High Risk Pregnancy (Report of a shotgun case) - Athare Nazri Panjaki; Maryam Haghighi; Meysam Zeynali Bujani; Mehdi Heidari (Mashhad University of Medical Sciences, 2018)
Introduction: Trauma is considered as one of the important factors of high risk pregnancies. Trauma is the most important cause of mortality among pregnant women and then fetus. The death caused by trauma during pregnancy is preventable; therefore knowledge regarding the immune principles of treating a pregnant mother is necessary. In this report, a beaten pregnant woman by shotgun is presented which in spite of a high risk pregnancy and longtime anesthesia, the mother and fetus condition return stable by proper and timely management of gynecologist and anesthesiologist,. Case presentation: The case is a 38 year-old women with gestational age of 32 weeks that a bullet was shot to her jaw and was ejected from the other side in Nov 2016. The bullet was also hit the shoulder area and the patient was intubated following shortness of breath. Three days later, the patient undergone general anesthesia with the presence of a gynecologist for 3 hours in order to perform Tracheostomy and jaw surgery and orthopedic surgery, and eventually the mother was recovered successfully. In the next day, because fetus condition was instable, emergency cesarean section was performed and finally the mother and neonate were discharged with good condition. Conclusion: In many cases, the death caused by trauma in pregnancy is preventable. When trauma happens, at first, the mother should be stabilized, then the monitoring of the fetus and uterine contractions are important part of dealing with trauma and the increased chance of mother and fetus health after the second trimester of pregnancy.